Factors Affecting Consumer Satisfaction among the Indian Young Youth Using Smart Phones: A Study - Jain, Stuti; Sarangdevot, Shiv Singh (International Journal of Computer Sciences and Engineering, 2019)
The smartphone industry is the fastest-growing sector in India. The smartphone industry has taken a long journey of 25 years from 1992 to 2018. During this 25 years of journey, mobile phones were transformed into personal computers. . It is growing at a very rapid pace and has a significant contribution to the Gross Domestic Product of India every year. . There is a great evolution of varied smartphones by different brands depending upon customer awareness and customer satisfaction. The new smartphones are featured with artificial intelligence, HD display, virtual assistant features like SIRI, Google assistant, etc., high-powered cameras, HD quality photos, Cloud storage feature, and better battery life. As per the study conducted by the mobile ecosystem forum, the highest penetration rate of smartphone users was in the age group of 16-35 years of old. The study of customer satisfaction is relevant for organizations to maintain long-term and healthy relationships with customers. In the presented thesis an effort has been made to understand the significant relationship between smartphone features and customers among Indian youth customers. An effort was also made to understand the significant relationship between the age, gender, income, and educational qualification of customers and awareness for the smartphone industry. It was finally concluded that smartphone features such as display, main camera, and touch battery life were the major contributing features in customer satisfaction (Indian young youth).